Peruvian health system: Proposal for a new model - Falconí Lázaro, Alejandro Raúl (Open Science Journal, 2020)
ABSTRACT This present study is carried out with the general objective of Proposing a New Health System Model based on the Praxeology of the actors that participate in the Health System Model of Peru, and as specific objectives (i) Analyze the Peruvian health system model from the subjectivities of its actors; (ii) Contrast jointly with the actors the models of Latin American health systems with the Peruvian health system model; (iii) Design the health system model for Peru from the perspective of the actors; (iv) Validate the proposed health system model for Peru; with reference to the bases of pragmatic paradigms, of complementarity, systemic, humanist and complexity. A mixed Derivative Sequential Exploratory study was conducted, contemplating the scope of transdisciplinary, projective research and multiple triangulation was applied. The study was presented in two successive phases, in the first, the theory based on the research method was chosen, 40 key participants were interviewed using the semi-structured in-depth interview; in the second, the exploratory research method, applying a questionnaire to 1308 participants nationwide. The results on the analysis, a negative rating was determined: degree of user satisfaction of 10.7%, and it was determined that 89.3% agree with what a reform to the current model. Regarding the comparison with other models, it is was found that 89.3% believe that reforms applied in other countries must be implemented in our country. About the design of the model, it was found that 89.3% of the participants prefer a combination between public and private; the 91.6% that should be emphasized the implementation of health determinants; the 37.2%, of the models presented, prefer the Bismarck Model. Accordingly, a praxeological model for the Peruvian health system is proposed, that relegates the dilemma of preferences between public and private, that considers a comprehensive approach to health determinants; and progressively towards a Bismarck model.